Donors, politics and the question of post-colonial land restitution in Zimbabwe - Mahuku, Darlington Ngoni; Mbanje, Bowden B.C.; Kahuni, Panganai (LANGAA RPCIG, 2021)
Land restitution in Southern Africa has attracted much attention from the international “community” as it is embedded in (neo- )colonial history of racial dispossession and segregation. Its intrusion into the present has a bearing on donor-government relations especially regarding restoration of land to Black Zimbabweans. The donors have tended to emphasise the need to respect the (neo- )imperial rule of law, which in fact translates to the rule of (neo- )empire. As will be noted in the foregoing, (neo-)empire has tried to block recent land reclamation and restitution in Zimbabwe. Empire has relentlessly tried to force African governments to adhere and commit to neo-colonial law and parameters for land redistribution. Proponents of market-based land reforms namely, the World Bank, International Monetary Fund, some Non-Governmental Organisations and others grudgingly acknowledge that land restitution is a necessity in Southern Africa. They have however maintained that land restitution must be firmly entrenched within the [imperial] rule of law which is incidentally the rule of empire. The International “Community” emphasizes that the existing land problems, ownership and redistribution must not be “racialised” and yet land inevitably takes a race-based spatial character everywhere in the world, including Euro-America where Black Africans are not allowed to own land. Most institutions and international conventions have legal requirements for expropriation and limitations to government authority to expropriate land. Zimbabwe as a member of the international “community” is subject to international standards but the challenge is that the international standards are often 220 designed by dominant Western countries and institutions with financial and economic power to impose sanctions on African countries that refuse to comply with what they often feel is unfair and unjust. Helliker (2006: 127-30) notes that land reform involves three components, that is, land redistribution, land restitution and land tenure. However land tenure gives access to land and deals with the social organisation of production and under market led reform it may be done at the expense of redistribution. Agrarian reform relates to capitalist penetration in rural areas whilst land restitution is all about reclaiming stolen land. Land has to be given back to Blacks who were victims of land looting by the Whites: restitution goes beyond mere land redistribution. The Fast Track Land Reform Programme and restitution in Zimbabwe is a reflection of historic land inequalities, including dispossession of Africans, which dispossession was committed by agents and beneficiaries of colonialism (Melber, 2002: 2). It is in this context that President Mugabe has revitalised the experiences of Zimbabwe as a victim of (neo-)colonial injustices and has thus maintained that; “Zimbabwe will never be a colony again.” Zimbabwe has continued to be regarded by some countries as a rogue state and donor countries have blamed Harare for Zimbabwe’s continued economic decline. While the demonic songs about the decline of Zimbabwe erroneously presuppose that the economy was performing well for every Zimbabwean, the pre-reclamation economy was good only for the selected few enjoying colonial privileges, including the White commercial farmers. For the majority of peasants crammed in sandy soiled and poorly watered communal areas, life had never been easy since the establishment of these colonial reserves [now called communal areas] for Africans. Donors have maintained that other SADC member states must not follow the Zimbabwean land reclamations which they blame for Zimbabwe’s plunge into being a basket case that can no longer afford to feed itself. However, there is evidence that much of the food in postcolonial Zimbabwe was produced by communal farmers and especially since the economic structural adjustment programmes in the 1990s, commercial farmers have focused increasingly on producing non-food crops for the international market. This chapter 221 explores how land reforms and restitution have unfolded. Given that ordinarily governments have the prerogative to restitute land in accordance to their own Constitutions and laws, the central question is: Under what conditions are governments likely to embark on land restitution within the rule of law? Why has “the law of the land” and the need for political justice in Zimbabwe been used to largely legitimise forceful, coercive actions that have worsened relations between the government and donors. The chapter also seeks to examine why the land question became political and thus directly challenging to the resilient empire. Land ownership in Zimbabwe has been affected and complicated by its colonial...